Relationship between community physical activity levels, social capital, intergenerational support, and subjective well-being among older adults in China: a moderated mediation model - Lin, Yuanzheng; La, Changxu; Luo, Qingyuan; Zhang, Peng (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the mediating role of social capital in the effect of community physical activity on older adults’ subjective well-being and the moderating role of intergenerational support.MethodsQuestionnaire data were collected from 318 older adults from China who participated in community-based physical activity using a random sampling method with the Physical Activity Scale, the Social Capital Scale, the Intergenerational Support Scale, and the Subjective Well-Being Scale. Data were analyzed by SPSS 25.0, PROCESS 3.4 and AMOS 24.ResultsCommunity physical activity positively affected older adults’ subjective well-being (β = 0.539, p < 0.001), and social capital mediated the effect of community physical activity on older adults’ subjective well-being (β = 0.162, p < 0.001, 23.11% of the total effect). Intergenerational support moderated the relationship between community physical activity and older adults’ subjective well-being (β = 0.133, p < 0.001).ConclusionActive participation in community physical activity can directly improve the subjective well-being of older persons on the one hand, and indirectly improve well-being by increasing social capital on the other. In addition, good intergenerational relationships can lead to more active participation in community physical activity, which in turn affects the subjective well-being of older people.